2020
DOI: 10.1097/md.0000000000023719
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic capecitabine as maintenance treatment after first line induction with XELOX for metastatic colorectal cancer patients

Abstract: Maintenance treatment after first-line chemotherapy for patients with metastatic colorectal cancer (mCRC) is a priority strategy. However, which medicine is chosen is controversial. This study aimed to determine the efficacy and safety of maintenance treatment with metronomic capecitabine vs observation. In this randomized controlled trial, patients who completed 18 weeks of induction chemotherapy with XELOX and achieved disease control were randomly assigned centrally (1:1) to receive maintenance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…The first patient enrollment started in July 2010. 16 Two were published as full texts, 16 19 and one trial has not been published but available with a conference presentation. 20…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first patient enrollment started in July 2010. 16 Two were published as full texts, 16 19 and one trial has not been published but available with a conference presentation. 20…”
Section: Resultsmentioning
confidence: 99%
“…In terms of safety outcomes, any adverse events were reported in one study 20 while all studies reported grade ≥ 3 adverse events. 16 19 QoL was assessed and reported in one trial using Eq. (5D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For mCRC, the role of mCap ± BVZ has shown encouraging results in palliative settings and maintenance therapy for 1 stline responders [27]. In HCC, mCap improved OS compared to BSC beyond sorafenib, with better results in good performance patients (18).…”
Section: Expert Opinionmentioning
confidence: 99%